2024
DOI: 10.1109/tnnls.2022.3229161
|View full text |Cite
|
Sign up to set email alerts
|

Deep Neural Networks and Tabular Data: A Survey

Abstract: Heterogeneous tabular data are the most commonly used form of data and are essential for numerous critical and computationally demanding applications. On homogeneous datasets, deep neural networks have repeatedly shown excellent performance and have therefore been widely adopted. However, their adaptation to tabular data for inference or data generation tasks remains highly challenging. To facilitate further progress in the field, this work provides an overview of state-of-the-art deep learning methods for tab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
80
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(146 citation statements)
references
References 176 publications
6
80
0
Order By: Relevance
“…This study found that the TabTransformer compared to other DNN (Densenet and FeedForward) and regularized Cox models showed a superior discriminative ability to predict NDs events in an older general population. Due to the attention-based layers, TabTransformer performs well with heterogeneous data, particularly in managing categorical input, which is not the case with other neural networks [18]. In time-dependent assessment, Tab-Transformer, compared to the other models, performed similarly in AUC and balanced accuracy, slightly worse in sensitivity and better in specificity at the 4th and 6th years of follow-up.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This study found that the TabTransformer compared to other DNN (Densenet and FeedForward) and regularized Cox models showed a superior discriminative ability to predict NDs events in an older general population. Due to the attention-based layers, TabTransformer performs well with heterogeneous data, particularly in managing categorical input, which is not the case with other neural networks [18]. In time-dependent assessment, Tab-Transformer, compared to the other models, performed similarly in AUC and balanced accuracy, slightly worse in sensitivity and better in specificity at the 4th and 6th years of follow-up.…”
Section: Discussionmentioning
confidence: 93%
“…DNNs also can handle survival time if the DNN algorithm is tailored to censored data by with the appropriate censoring unbiased loss functions [15][16][17]. The disadvantages are that most DNNs do not perform appropriately with heterogeneous tabular data [18]. Researchers have recently developed algorithms with different structures that can deal with tabular-heterogeneous data to fill this gap [18] Still, these algorithms have not been widely investigated yet to time-to-event outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Classification tasks on tabular data have been widely studied in the machine learning literature [23], [24]. One popular approach for such tasks is the use of decision tree-based algorithms, such as Random Forests [25] and XGBoost [26].…”
Section: Related Workmentioning
confidence: 99%
“…As long as there is correlation between the input information and the output, the models will discover it. In order to use deep learning, the input software features are written in tabular form, a data form that has been extensively researched and for which many models are available [9].…”
Section: Introductionmentioning
confidence: 99%